Work-Domain Goal Orientation: A Theoretical Framework for the Construct and Turkish Adaptation of a Work-Domain Goal Orientation Instrument - Aysun Gurol; Dilek Ilhan Findikoglu; Mehmet Gurol; Fuat Findikoglu; Mehmet Yesilkaya (Education Sciences)
This study brings a novel perspective to the relationship between higher education and work life by examining work-domain goal orientation as a critical factor in preparing students for professional environments. Through an extensive literature review, it highlights the role of work-domain goal orientation in aligning higher education curricula with the demands of the modern workplace, emphasizing how students’ goal orientation influences their future professional success. Additionally, this study adapts and validates a work-domain goal orientation instrument into Turkish, offering a reliable tool for use in Turkish contexts. A sample of 729 undergraduate students from various academic disciplines participated in the study. Exploratory and confirmatory factor analyses confirmed a three-factor structure (learning, proving, avoiding), accounting for 68.4% of the variance. The internal consistency was reliable, with Cronbach’s alpha values ranging from 0.84 to 0.86 across subscales. The study provides a dual contribution by offering theoretical insights into work-domain goal orientation and delivering a psychometrically validated tool for assessing students’ readiness for professional life in a non-Western context. These findings address gaps in the literature on goal orientation and its application in diverse cultural settings, advancing both academic understanding and practical applications for educational institutions and employers. This study contributes to bridging the gap between higher education and work life, offering both theoretical perspectives and a practical tool to improve workforce preparedness.